Improving Students' Indonesian Language Learning Outcomes through the Planted Questions Active Learning Method in Grade V at MI NW Bagik Nyala - Nurul Hudaini; Jumatriadi (Journal of Education, Teaching, and Learning, 2026)
Improving students’ Indonesian language learning outcomes remains a significant challenge in elementary education, particularly in developing active participation, critical thinking, and meaningful learning experiences. This study aimed to examine the effectiveness of the Planted Questions Active Learning method in improving Indonesian language learning outcomes among Grade V students at MI NW Bagik Nyala. This research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. The research subjects were Grade V students, and data were collected through learning outcome tests, classroom observations, and documentation. The collected data were analyzed using qualitative and quantitative descriptive analysis to identify changes in students’ learning achievement and classroom engagement. The findings revealed that the implementation of the Planted Questions Active Learning method contributed to significant improvements in students’ Indonesian language learning outcomes. In the first cycle, students showed initial improvements in participation and understanding, although several students still experienced difficulties in expressing ideas and comprehending learning materials. After the improvements implemented in the second cycle, students demonstrated higher achievement, increased confidence, active involvement in discussions, and better understanding of Indonesian language concepts. The study concludes that the Planted Questions Active Learning method is an effective instructional strategy for enhancing students’ learning outcomes by creating a more interactive, collaborative, and student-centered learning environment. This research implies that elementary school teachers can utilize this method as an alternative approach to improve the quality of Indonesian language instruction..